The Effect of Audit Tenure on Audit Quality in Companies Listed on the Indonesia Stock Exchange - Dito Aditia Darma Nst; Najwa Rahmadini; Jessica Dwi Yolanda Pandiangan; Annisa Ramadhani; Iin Sri Ayu Sihotang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of audit tenure on audit quality at PT Wijaya Karya (Persero) Tbk, which is listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach with a causal associative research method. The data used are secondary data obtained from the company’s annual reports and financial statements. Data collection was conducted through documentation, while sample selection used purposive sampling. The data analysis method applied was simple linear regression to examine the effect of audit tenure on audit quality. The results indicate that audit tenure has a significant effect on audit quality, suggesting that the length of the relationship between the auditor and the client has implications for the quality of audit outcomes. These findings are expected to contribute to the development of accounting literature and serve as a consideration for regulators and companies in determining auditor engagement policies to maintain audit quality.